KARAKTERISTIK SPIRITUAL QUOTIENT PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH PERTAMA - Farikhin, Muhammad (Hidmah : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Islamic religious education at Nurul Anwar Islamic Middle School helps students improve their spiritual intelligence in several ways, one of which is by incorporating religious culture into the classroom, as this study shows. The Pai curriculum at Nurul Anwar Islamic Middle School places a strong focus on spiritual harmony, which increases the capacity to instill moral values based on three important and interconnected Islamic principles: faith, Islam, and ihsan. This study aims to determine various aspects of spiritual intelligence (SQ) in PAI education and how it relates to contemporary Islamic education. This research uses a certain type of field research, or field research that uses descriptive research methods. qualitative. Primary data and secondary data are two different categories of data sources. While data collection is done through observation, interviews, and documentation.